If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -36 = 9(t + -97) + -45 Reorder the terms: -36 = 9(-97 + t) + -45 -36 = (-97 * 9 + t * 9) + -45 -36 = (-873 + 9t) + -45 Reorder the terms: -36 = -873 + -45 + 9t Combine like terms: -873 + -45 = -918 -36 = -918 + 9t Solving -36 = -918 + 9t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-9t' to each side of the equation. -36 + -9t = -918 + 9t + -9t Combine like terms: 9t + -9t = 0 -36 + -9t = -918 + 0 -36 + -9t = -918 Add '36' to each side of the equation. -36 + 36 + -9t = -918 + 36 Combine like terms: -36 + 36 = 0 0 + -9t = -918 + 36 -9t = -918 + 36 Combine like terms: -918 + 36 = -882 -9t = -882 Divide each side by '-9'. t = 98 Simplifying t = 98
| -4x^2+11x=7 | | 9n=8n+15 | | -(3y+2)-(-2y-7)=3 | | 3(5x+1)=-2x-8 | | 5x+10=3x+18 | | 4x-5y=22 | | 10x-(7x+4)=8 | | 5(3+4X)-5=70 | | 3846.5=3.14*r^2 | | 4r+2b=2y | | -5(-4x-2)=9x | | 1/8x=-7 | | 9x+16=3x+2 | | x+20=-47 | | 0.3(x-1)-0.45x=1 | | a+16=-10a | | 3c-3b-2c-b= | | 106.76=2r*3.14 | | 4x-5y=28 | | 3a+5b=3c | | 6x+34+8=10 | | 96=8(d+3)+8 | | 4a+2b=2c | | 8x-(5x-5)=20 | | 4x-6+8x=3x+6 | | -x+4(2)=-20 | | -3y=-2x-10 | | 2x+13-7x=19-19x+14x-6 | | f(x)=3x^2-10x+3 | | 2x+10(2)=-20 | | 1(x+4)-40=3x-10 | | F(x)=(x^2)+3x+2 |